Occurrence of post-endodontic pain after single-visit RCT using Balanced Force technique and two reciprocating system when apical patency is maintained - Paredes Vieyra, Dr. Jorge; Ocampo Acosta, Fabian; Jiménez Enriquez, Francisco Javier; Rojas Alvarado, Rosendo Andres (International Journal of Scientific Research and Management (IJSRM), 2018)
Aim. The goal of this research was to relate the occurrence of post-endodontic pain after single-visit RCT using Balanced Force technique and two reciprocating system when AP is conserved.Methodology: Two hundred and sixteen of 245 patients aged 18-65 years were incorporated in this research. All patients had teeth selected for conventional RCT for prosthetic reasons detected with only vital pulps. For hand instrumentation, Balanced Force were used. All canals were clean and shaped with hand Flex-R files. For mechanical shaping, all instruments were prepared with Protaper Next and Reciproc instruments in continuous brushing and reciprocating mode respectively. Final irrigation with cold (8oC) 17% EDTA served as a lubricant.Results: The average age of the 216 participants registered in this research was 54 years. No statistically significant difference (p > .05) among the groups were found regarding degree or duration of pain. There was no statistically significant difference (p> .05) among the Balanced Force technique, PTN and R techniques in relation to the occurrence of post/endodontic ache at any of the three time points measured (Table 3, 4).Conclusions. The incidence of post-endodontic pain is lower when AP is maintained and presence/absence of pre-operative pain has to be consider. When previous symptoms are present, occurrence and period of pain is longer in teeth with this condition that when AP is maintained. It can be established that conserving AP with a thin K-file can help to prevent post-endodontic pain in some specific cases.